Emergency department crowding in the Netherlands; evaluation of a real-time ambulance diversion dashboard - E. C. M. Baan-Kooman; S. Mol; M. C. van der Linden; M. I. Gaakeer; V. A. de Ridder (International Journal of Emergency Medicine, 2025)
Abstract Background Emergency department (ED) crowding is a growing concern worldwide and associated with negative effects. In 2013, 68% of Dutch ED-managers experienced crowding on several days of the week. This resulted into the introduction in phases of an ambulance diversion dashboard, in order to influence ED input. Increasing numbers of Dutch EDs have implemented this dashboard, visualizing regional ambulance diversions by means of a traffic light. Methods This is a descriptive study of a nationwide online survey of Dutch EDs, conducted between January and October 2023. It included both qualitative and quantitative questions. The outcomes and analysis are derived from descriptive data of respondents’ experience of crowding as well as their usage and perceived effectiveness of the ambulance diversions dashboard. Results At the time of the survey, 62 of 82 Dutch EDs (75.6%) actually used the dashboard, of which 56 EDs responded (90.3% response rate). 69.7% Of ED managers experienced ED crowding more than three times a week. Of the respondents using the dashboard, 52.8% reported it only occasionally alleviates ED inflow. The purported reasons are the limited number of patients affected by the red light (ambulance diversion) and the presence of regional crowding. The effects of the orange light (impending ambulance diversion) on ED input differ greatly among hospitals, mostly due to their own internal agreements. In accordance, many respondents (53.6%) expressed dissatisfaction with the resources available to them to alleviate crowding. Conclusion After conducting a national survey, ED crowding is reported as a persisting nationwide problem with its prevalence largely unchanged since the introduction of the ambulance diversion dashboard. Most hospitals reported having insufficient resources to alleviate it. The effects of the ambulance diversion dashboard to decrease crowding are apparently limited because it affects a small portion of total ED presentations and because of the influence of regional crowding. The main function of the orange light is to increase ED throughput and output rather than reducing ED input.